PEMETAAN TEMATIK KESESUAIAN LAHAN BUDIDAYA RUMPUT LAUT PADA PERAIRAN TELUK KAYELI KABUPATEN BURU - Sangur, Kristin; Koto, Saifuddin; Irsan, Irsan; Moningka, Vincentius F D; Bastian, Putri M A; Nuraisah, Siti; Hamid Pelupessy, Iskandar Abd (Program Studi Pendidikan Biologi FKIP Unpatti, 2024)
Background: Seaweed is widely cultivated in coastal areas of Indonesia, one of which can be found in Kayeli Bay, Buru Regency. One of the problems faced by farmers in cultivating seaweed in this area is that there is no division of suitable areas for cultivation land in the form of thematic maps, especially using physical-chemical parameters of waters. Methods: This activity includes several stages, namely location survey, data collection or collection and preparation of a database. Measurements of physical and chemical parameters of waters are carried out directly in the field (in situ) and in the laboratory (ex situ). The measurement parameters include temperature, brightness, wave height, current speed, pH, salinity, DO, nitrate and phosphate. To create a thematic map of land suitability, the ArcGis application was used. Results: Most of the physical and chemical parameters of the waters are still suitable for seaweed cultivation, except for temperature and phosphate. The results of land suitability evaluation/analysis based on water physical-chemical parameters produce two land suitability categories, namely suitable (S2) and very suitable (S1). The category corresponds to an area of ​​110.2 ha or 29% and very corresponds to an area of ​​269.8 ha or 71%. Conclusion: The thematic map of Kayeli Bay waters, Buru Regency shows that the suitability of seaweed cultivation land is divided into two categories, namely suitable at 29% and very suitable at 71%. However, the temperature and phosphate parameters at the time of measurement were in the category not suitable for seaweed cultivation.